2017
DOI: 10.1038/nature21705
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive termination of the hypoxic response by a disordered protein switch

Abstract: The cellular response to hypoxia is critical for cell survival and is fine-tuned to allow cells to recover from hypoxic stress and adapt to heterogeneous or fluctuating oxygen levels1,2. The hypoxic response is mediated by the α subunit of the transcription factor HIF-1 (HIF-1α)3, which interacts via its intrinsically disordered C-terminal transactivation domain with the TAZ1 (CH1) domain of the general transcriptional coactivators CBP and p300 to control transcription of critical adaptive genes4–6. One such g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
279
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(302 citation statements)
references
References 30 publications
22
279
1
Order By: Relevance
“…The lowest basin corresponds to CITED2 bound state (CB state, 0.00 kT), which means that TAZ1-CITED2 is the dominant state of all. This is consistent with the NMR results of ref 15 Fig. 2 The free energy surface at experimental temperature as a function of Q inter (TAZ1-HIF-1α) and Q inter (TAZ1-CITED2), as well as the main states on the free energy surface (HB1 is not a basin on free energy surface but an area near HB state with part of CITED2 bound).…”
Section: Thermodynamic Mechanism Of Ternary Taz1-hif-1α-cited2 Complexsupporting
confidence: 90%
See 3 more Smart Citations
“…The lowest basin corresponds to CITED2 bound state (CB state, 0.00 kT), which means that TAZ1-CITED2 is the dominant state of all. This is consistent with the NMR results of ref 15 Fig. 2 The free energy surface at experimental temperature as a function of Q inter (TAZ1-HIF-1α) and Q inter (TAZ1-CITED2), as well as the main states on the free energy surface (HB1 is not a basin on free energy surface but an area near HB state with part of CITED2 bound).…”
Section: Thermodynamic Mechanism Of Ternary Taz1-hif-1α-cited2 Complexsupporting
confidence: 90%
“…The NMR experiments of Wright et al 15 observed that TAZ1-CITED2 complex is dominant in the TAZ1:HIF-1α:CITED2 solvation with 1:1:1 molar ratio. The fluorescence anisotropy competition experiments found that CITED2 exhibits an apparent K d of 0.2±0.1 nM to TAZ1-HIF-1α complex, while HIF-1α displaces TAZ1-bound CITED2 with a much higher apparent K d (0.9±0.1 µM) 15 . These experimental results indicate that CITED2 is extremely effective in displacing HIF-1α from the TAZ1-HIF-1α complex.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Structural disorder is often advantageous for proteins that perform multiple roles, interact with numerous partners, or rapidly transition between conformational states (Wright and Dyson, 2015). In the case of HIF-1a, protein disorder is proposed to enable efficient protein partner switching even when cellular concentrations of competing partners are similar (Berlow et al, 2017). Whether unstructured regions of NepR enable partner switching between equimolar PhyR and r EcfG remains to be determined and requires additional experimentation.…”
Section: A Ternary Complex Between Phyr Nepr and R Ecfg Underlying Pmentioning
confidence: 99%